The surgical approach for clipping anterior communicating artery Aneurysm - Bhattarai, Robin; Chen, Chuan; Liang, Chao Feng; Huang, Teng Chao; Wang, Hui; Ling, Cong; Guo, Ying (Nepal Journal of Neuroscience, 2019)
Anterior communicating artery (ACoA) aneurysm, accounts for 30%-35% of all the aneurysm making it one of the most common intracranial aneurysms. Although the Pterional approach is considered as the safe and appropriate method in ACoA aneurysm surgery, temporalis atrophy and injury to a frontal branch of the facial nerve are few inexorable complications. With the advancement of minimally invasive surgery several modified approaches, such as the supraorbital eyebrow incision approach, the minipterional approach, the mini-supraorbital approach, and the lateral supraorbital approach has been recently introduced and has been used as an alternative.